Assessing critical thinking skills in vocational school students during hybrid learning - Asrowi, Asrowi; Maulana, Iwan; Budiarto, Mochamad Kamil; Qodr, Taufiq Subhanul (Intelektual Pustaka Media Utama, 2025)
In the current educational landscape, the development of critical thinking abilities is becoming increasingly important, especially considering the prevalence of hybrid learning methods. This investigation aimed to evaluate the proficiency of critical thinking skills in students who are immersed in hybrid learning. A descriptive quantitative research approach was employed, utilizing observation, documentation, and critical thinking assessments to collect data from a sample of 60 students from vocational high schools. The findings highlight two main results: firstly, the majority of students demonstrate a low level of critical thinking skills within the hybrid learning context, indicating the need for improvement; secondly, various factors that influence these skills were identified. These outcomes emphasize the challenges associated with acquiring 21st-century skills and emphasize the necessity for collaborative efforts. Both educators and students must enhance their commitment to effective learning preparation, with a particular emphasis on motivation to foster improved critical thinking abilities. This research provides valuable insights for educators and policymakers who are striving to enhance the hybrid learning environment in order to better cultivate critical thinking skills in students.